Environmental Factors of Samarkand Region and Their Impact on Nature - Eshmonova Bahoroy (American Journal of Biology and Natural Sciences, 2024)
This article provides detailed information about the environmental factors of Samarkand region and their impact on the region’s nature. The article focuses on important issues such as climate change, water resource scarcity, land degradation, and the impact of human activities on the environment. Recommendations for environmental conservation and addressing environmental problems are also presented.